Structural chemistry and magnetic properties of hexagonal perovskites BaIrxMn1-xO3, x=0.3, 0.4, 0.5 - Jordan, N; Battle, P (2003)
The crystal structures and magnetic properties of BaIrxMn 1-xO3, x = 0.3, 0.4, 0.5, have been investigated using a combination of X-ray and neutron powder diffraction, and d.c. magnetometry. The hexagonal 9R perovskite structure (space group R3̄m, a ≈ 5.7 Å, c ≈ 21.4 Å), built up from corner-sharing trimers of face-sharing octahedra, is adopted across the series. High resolution neutron diffraction data confirm that the Mn4+ and Ir4+ cations exist in a disordered distribution across the two octahedral cation sites and indicate that for each composition, the oxygen content is stoichiometric. Low temperature neutron diffraction studies revealed the presence of a long-range magnetic order at 5 K consistent with an antiferromagnetic arrangement of spins. A combination of d.c. magnetometry and neutron diffraction has allowed the Néel temperature (TN) of BaIr0.4Mn 0.6O3 to be identified as 100(5) K, whilst TN for BaIr0.3Mn0.7O3 is 135(5) K. The susceptibility data also provide evidence that a proportion of the spins remain decoupled from the long-range antiferromagnetically ordered state and that a transition which involves the freezing of these spins in a glassy manner occurs at Tf = 45(1) K for each sample.